Homogenization of climate data - Costa, Ana Cristina (2019)
Costa, A. C., & Soares, A. (2009). Homogenization of climate data: Review and new perspectives using geostatistics. Mathematical Geosciences, 41(3), 291-305. https://doi.org/10.1007/s11004-008-9203-3